2004
DOI: 10.1258/002221504323086642
|View full text |Cite
|
Sign up to set email alerts
|

Unusual complication of parotid abscess

Abstract: Temporal lobe abscess as a complication of parotid abscess is not described in the English literature. In this case report a 66-year-old gentleman is described who presented with a left-sided parotid abscess, which extended to other deep neck spaces, and advanced to develop a temporal lobe abscess and subdural parietal empyema. Treatment included intravenous antibiotics, incision and drainage of parotid abscess, and burr hole aspiration of the temporal lobe abscess. The importance of imaging to evaluate the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A parotid abscess, in some cases, can be a life threatening disease, as the inflammation can spread to the head and neck causing the formation of abscesses in these zones [5].…”
Section: Introductionmentioning
confidence: 99%
“…A parotid abscess, in some cases, can be a life threatening disease, as the inflammation can spread to the head and neck causing the formation of abscesses in these zones [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies reported wound healing problems, which were not observed in our study [9]. Severe complications such as jaw osteomyelitis, temporal lobe abscess [23] craniocervical necrotizing fasciitis [24], descending mediastinitis [25], airway obstruction, septicemia, and septic shock [11,25,26] did not occur during the follow-up of our patients.…”
Section: Discussionmentioning
confidence: 40%
“…6 The predisposing conditions of acute suppurative parotitis include dehydration, poor oral hygiene, dental infection, oral trauma, ductal obstruction, immunosuppression, certain drugs (anticholinergics and antihistamines), certain chronic diseases (Sjogren's syndrome and diabetes mellitus), malnutrition, pre-existing parotid Warthin's tumor, and sialolithiasis. 7,8 These precipitating factors generally seen in adults. Ductal stones not seen frequently in children as in our case, correlating the fact that parotid abscess formation is related with nonobstructive origin in most cases.…”
Section: Discussionmentioning
confidence: 99%